2013
DOI: 10.1007/s10113-013-0563-y
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic impacts of climate change on flood frequency using response surfaces I: England and Wales

Abstract: The impacts of climate change on hydrology are an important focus of research around the world, but use of large ensembles to drive impact models is not necessarily straightforward and has to be re-done when new projections are released. Here an alternative sensitivity framework approach is demonstrated, using a set of typical response surfaces alongside the probabilistic UK Climate Projections (UKCP09). These projections comprise sets of 10,000 changes in a number of variables, available for 10 river-basin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Maps summarising the studies listed in supplementary table S1 by (a) the effect they showed on peak flows and (b) whether they were based on observed or modelled data. High), were processed and overlaid on the representative flood response surfaces, and corresponding sets of flood impacts extracted (Kay et al 2014a(Kay et al , 2014b. Here the impacts on 50 year return period flood peaks are used, as the current Environment Agency guidance on climate change and flood peaks is based on these values (Reynard et al 2017).…”
Section: Impacts Of Climate Change On Flood Peaksmentioning
confidence: 99%
See 1 more Smart Citation
“…Maps summarising the studies listed in supplementary table S1 by (a) the effect they showed on peak flows and (b) whether they were based on observed or modelled data. High), were processed and overlaid on the representative flood response surfaces, and corresponding sets of flood impacts extracted (Kay et al 2014a(Kay et al , 2014b. Here the impacts on 50 year return period flood peaks are used, as the current Environment Agency guidance on climate change and flood peaks is based on these values (Reynard et al 2017).…”
Section: Impacts Of Climate Change On Flood Peaksmentioning
confidence: 99%
“…These decision trees were applied to each catchment in the National River Flow Archive (NRFA; nrfa. ceh.ac.uk), to provide information on the spatial distribution of flood response types across Britain (Kay et al 2014a(Kay et al , 2014b; supplementary figure S2). Extra uncertainty allowances were also derived for each response type (Kay et al 2014c).…”
Section: Impacts Of Climate Change On Flood Peaksmentioning
confidence: 99%
“…Reynard et al ., ; Prudhomme et al ., ; Booij, ) and regions (e.g. Bell et al ., ; Garcia‐Ruiz et al ., ; Kay et al ., ,b). In addition, Lehner et al .…”
Section: Future Changementioning
confidence: 99%
“…Hybrid selection approaches have been proposed consisting of a combination of two or more of these methods, while sensitivity-based methods have been used for generating climate impact response surfaces for which projected changes in climate variables can be directly translated into impacts [12].…”
Section: The Fifth Coupled Model Intercomparison Project (Cmip5) Provmentioning
confidence: 99%